Resveratrol attenuates lipopolysaccharide-induced hepatitis in D-galactosamine sensitized rats: role of nitric oxide synthase 2 and heme oxygenase-1 - Farghali, Hassan; Cerný, Dalibor; Kameníková, Ludmila; Martínek, Jindrich; Horínek, Ales; Kmonícková, Eva; Zídek, Zdenek (Nitric oxide, 2009)
The goal of study was directed to investigate the effects of resveratrol (RES) pretreatment on the enhancing action of D-galactosamine (D-GalN; 800 mg/kg) on lipopolysaccharide (LPS; 0.5 microg/kg) inducing liver failure in rats. Liver function was assessed by determination of plasma alanine aminotransferase (ALT), aspartate aminotransferase (AST), alpha-glutathione S-transferase (alpha GST) and bilirubin (BILI). Plasma NO(2)(-) was assessed by NO(2)(-)/NO(3)(-) colorimetric kit. The estimation of nonenzymatic and enzymatic antioxidants (glutathione and catalase) was performed in plasma and liver homogenate. Lipid peroxidation was evaluated by the thiobarbituric acid reacting substances (TBARS) and the conjugated dienes (CD). Morphological examinations using light and electron microscopy were performed. Observations related to pharmacological increases of inducible nitric oxide synthase (NOS-2)/nitric oxide (NO) and inducible heme oxygenase (HO-1) in fulminant hepatic failure and modulation by resveratrol were followed up by real-time reverse transcription PCR (RT-PCR) in liver tissue. In the present study we found that among the mechanisms responsible for the hepatoprotective effect of resveratrol in the LPS/D-GalN liver toxicity model are reduction in NO, downregulation of NOS-2, modification of oxidative stress parameters and modulation of HO-1 which led to overall improvement in hepatotoxic markers and morphology after the hepatic insult.
Keywords: oxidační stres; antioxidancia; Galactosamine; Male; Lipopolysaccharides; Rats, Wistar; lékové postižení jater; lipopolysacharidy; hemová oxygenasa (decyklizující); Nitric Oxide Synthase Type II; Resveratrol; cytoprotekce; galaktosamin; mužské pohlaví; potkani Wistar; Cytoprotection; Liver Failure; krysa rodu Rattus; Heme Oxygenase (Decyclizing); stilbeny; Animals; játra; Antioxidants; Stilbenes; zvířata; Rats; peroxidace lipidů; synthasa oxidu dusnatého, typ II; resveratrol; Lipid Peroxidation; Liver; Oxidative Stress; Chemical and Drug Induced Liver Injury; selhání jater